Sindrome de Poland: Un caso con dextrocardia. - TORI TORI, Carlos; SABOGAL CARREÑO, Alberto (Revista Médica Herediana, 2013)
We report on a case of Poland anomaly (defect of the muscle pectoralis major and symbrachydactyly on the same side) with dextrocardia. The absence of the pectoralis major muscle without the limb anomaly can be a variant of the Poland sequence (1).While most of the reported cases of this syndrome is in the right side (2) and without rib defects, in our patient the anomaly was on the left side, accompanied by dextrocardia and with anomalies of the rib cage.